UPM and Sri International collaborate to commercialize research work - New Sunday Times, (2009)
In an to enable its researchers to attain greater height , Universiti Putra Malaysia (UPM) has entered into a Memorandum of Agreement (MOA) with Sri International to collaborate on service and training pertaining to commercialisation measures.